Surface modifying macromolecules for enhancement of polyethersulfone pervaporation membrane performance. - Pham, Vu Anh. (University of Ottawa (Canada), 1995)
The objective of this work was to modify the surface of polyethersulfone membranes in order to render them more useful in pervaporation for the removal of volatile organic compounds (VOC) from aqueous solutions. Surface Modifying Macromolecules (SMNs) were designed and developed as surface modifiers of asymmetric polyethersulfone (PES) membranes. Eight SMM polymers were synthesized in triplicate using methylene bis-p-phenyl diisocyanate (MDI), polypropylene oxide (PPO) and polyfluoroalcohol (BA-L). They represented a 2$\sp3$ factorial design used to study the effects of reactant stoichiometry, prepolymer reactant concentration and chain length of the polyfluoroalcohol on the SMM properties and reproducibility of the SMM synthesis. The bulk SMM polymers were characterized with differential scanning calorimetry (DSC), gel permeation chromatography (GPC) and elemental analysis. The compatibility between PES and SMM polymers was studied by DSC. The average molecular weight of SMM polymers, determined by GPC, were in the range of $1.0\times10\sp4\rm\ to\ 3.5\times10\sp4$. As predicted by theoretical considerations, SMMs were found to have migrated to the PES surface, rendering it more hydrophobic. This migration effect was confirmed by water droplet contact angle measurements and X-ray photoelectric spectroscopy (XPS). Opaqueness of PES/SMM films and results of DSC showed that SMM was either immiscible or partially miscible with PES. Preliminary pervaporation studies indicated that the addition of SMMs improved the selectivity of PES membranes, used in the separation of chloroform/water mixtures by 150 to 240%, depending on the chemical formulation of the SMM. In several cases, SMMs also improved the permeation rate. From a preliminary assessment of the changes in membrane surface and bulk characteristics, the surface chemistry and energetics were observed to contribute an important role in inducing the membranes' enhanced properties. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.